Luminescence of Pb(2+) in MAl(2)B(2)O(7) (M = Ca, Sr) - (:unkn) unknown (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2008)
Pb(2+) doped SrAl(2)B(2)O(7) was prepared by solution combustion synthesis. The synthesized material was determined by powder XRD. The photoluminescence properties of the synthesized phosphor were investigated at room temperature using a spectrofluorometer. The emission peak of Pb(2+) doped SrAl(2)B(2)O(7) was observed at 420 nm upon excitation at 277 nm. The Stokes shift of SrAl(2)B(2)O(7):Pb(2+) was calculated to be 12 292 cm(-1). The luminescence behavior of Pb(2+) in both SrAl(2)B(2)O(7) and CaAl(2)B(2)O(7) was discussed.
Keywords: SRAL2B2O7; CAAL2B2O7; EU3+; TB